A Mendelian randomization study on the causal effects of circulating cytokines on the risk of vitiligo - Liu, Chengling; Liu, Xingchen; Xin, Haiming; Li, Xin (Frontiers in Medicine, 2024)
Background: Accumulating evidence reveals an association between circulating cytokine levels and vitiligo. However, the causal association between circulating cytokine levels and vitiligo remains undetermined.We performed a two-sample Mendelian randomization (MR) analysis using a genome-wide association study of 41 cytokines dataset, which was conducted with three Finnish cohorts (n=8,293). Vitiligo data were acquired from strictly defined vitiligo data collected by FinnGenbiobank analysis, which included 207,613 European ancestors (131 vitiligo patients, 207,482 controls). The inverse variance weighted method (IVW), weighted median (WME), simple model, weighted model, and MR-Egger were used to determine the changes of vitiligo pathogenic cytokines taxa, followed by sensitivity analysis, including horizontal pleiotropy analysis. The MR Steiger test evaluated the strength of a causal association and the leave-one-out method to assess the reliability of the results. The possibility of reverse causality was also investigated using a reverse MR study.We observed that rising IL-4 levels generated an enhanced probability of vitiligo in IVW (OR 2.72, 95%CI 1.19-6.22, p=0.018). According to the results of the MR analysis, there were causal links between IL-4 and vitiligo. Results were steady after sensitivity and heterogeneity analysis.Our research reveals that a genetically determined raised level of circulating IL-4 may be linked to a higher risk of developing vitiligo. The development of innovative treatment (such as Tofacitinib or Dupilumab) approaches that focus on blocking IL-4 as a novel way of preventing and treating vitiligo is significantly impacted by our findings.